1986
DOI: 10.1073/pnas.83.18.6766
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and processing of insulin precursors in yeast.

Abstract: A series of dibasic insulin precursors including proinsulin was expressed and secreted from Saccharomyces cerevisiae. Recombinant plasmids were constructed to encode fusion proteins consisting of a modified mating factor al leader sequence and an insulin precursor. The leader sequence serves to direct the fusion protein into the secretory pathway of the cell and to expose it to the Lys-Arg processing enzyme system. The secreted peptides were purified from the fermentation broth and characterized by sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(105 citation statements)
references
References 45 publications
3
100
0
2
Order By: Relevance
“…Kex2 functions late in the secretory pathway of Saccharomyces cerevisiae to cleave the polypeptide chains of prepro-killer toxin and prepro-a-factor at the paired amino acid sequences Lys-Arg and Arg-Arg. In addition to these natural functions, the Kex2 protease can mediate the processing of proinsulin and proalbumin expressed in yeast (21,22) and can properly cleave the propeptide of proalbumin in vitro (23). Finally, Kex2 can function in transfected murine cells to process proopiomelanocortin prohormone to product peptides normally found in vivo (11).…”
mentioning
confidence: 99%
“…Kex2 functions late in the secretory pathway of Saccharomyces cerevisiae to cleave the polypeptide chains of prepro-killer toxin and prepro-a-factor at the paired amino acid sequences Lys-Arg and Arg-Arg. In addition to these natural functions, the Kex2 protease can mediate the processing of proinsulin and proalbumin expressed in yeast (21,22) and can properly cleave the propeptide of proalbumin in vitro (23). Finally, Kex2 can function in transfected murine cells to process proopiomelanocortin prohormone to product peptides normally found in vivo (11).…”
mentioning
confidence: 99%
“…Greenfield et al (1988) have observed that the substance detected in this fungi, which somehow resembles mammalian insulin, exerts metabolic effect in mammalian adypocites. The insulin precursor expression and secretion, including proinsulin, was found in S. cerevisiae by Thim et al (1986). According to Lenard (1992) hormones and hormones binding proteins resembling those of vertebrates are widespread in fungi, yeast and bacteria, and functional responses of microbial cells to mamaliam hormone have been found.…”
Section: Discussionmentioning
confidence: 97%
“…The authors conceded that the fungi material obtained was similar to purified mammalian insulins in its solubility in acid-ethanol, elution profile, bioactivity in bioassay systems, and the neutralization of its bioactivity by anti-insulin antibody. The findings from Thim et al (1986) showed a series of dibasic insulin precursors including proinsulin expressed and secreted by the fungi Saccharomyces cerevisiae. Recombinant plasmids were constructed to encode fusion proteins consisting of a modified mating factor alpha leader sequence and an insulin precursor.…”
Section: Studies With Fungi (True Fungi)mentioning
confidence: 99%
“…Similar pressure has acted to conserve the length and overall net charge of the C peptide of proinsulin rather than the amino acid sequence [26]. It has been speculated, therefore, that such spacer peptides may function as 'second signal peptides' ensuring that the prohormone adopts the correct conformation for processing at the appropriate dibasic residues [27].…”
Section: A N G L E R F I S H I Imentioning
confidence: 99%